Medical research misconduct need regulatory reforms - Neeraj Bedi (Wolters Kluwer Medknow Publications, 2014)
The medical research misconduct has become a global problem. Except from countries like the USA, China, and Germany the exact figures of misconduct are not available. The research misconduct include fabricating the data, falsifying data, and plagiarism. The irresponsible research practices are publishing research data more than once, conflicts of interest is not declared, selective reporting of data and including an author who has not contributed at all and many more. About 2% of scientists have been found to admit the fabricating the data and 33% researchers were involved in irresponsible research practices. There is no formal regulatory programs available to monitor the research projects. Few developed countries like the USA, Germany, and China tried to develop programs which can monitor the medical research misconduct. There is a need to develop a regulatory system at national and institutional level to regulate the research activity to ensure that good ethical and scientific standards are practiced by medical researchers.